Pyrophosphate as substrate for alkaline phosphatase activity: A convenient flow‐injection chemiluminescence assay. (21st April 2017) - Zhang, Qingfeng; Zhang, Cuiyun; Yang, Meiding; Yu, Donghong; Yu, Cong
Abstract: A sensitive and convenient flow‐injection chemiluminescence (FI‐CL) turn‐on assay for alkaline phosphatase (ALP) activity without any label and synthesis is developed. Cu 2+ can catalyze the luminol–H2 O2 CL reaction. Pyrophosphate (PPi) can chelate Cu 2+ and therefore the Cu 2+ ‐mediated luminol‐H2 O2 CL reaction is inhibited. The addition of ALP can catalyze the hydrolysis of PPi into phosphate ions, Cu 2+ is released and the chemiluminescence recovers. A detection limit of 1 mU/mL ALP is obtained.